Developing Instruments: Student Academic Engagement Levels and Satisfaction with School Design - Lennie Scott-Webber; Roger Konyndyk; Raechel French (European Scientific Journal, ESJ, 2019)
This paper explores the relationship between student academic engagement and student satisfaction with the school building, both with the classroom and the building overall in the effort to build two new measurement instruments. This work was the third in a series investigating this same topic, each survey being a refinement of its predecessor. Consistent with the previous two trials, we showed that academic engagement and satisfaction with the school building’s design tends to go hand-in-hand, as measured by our surveys,. Of particular interest is the fact the effect of school design on engagement was consistent across schools, gender, and grade level. We also achieved very good results for survey reliability, and we are confident that the surveys are valid.